Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine: VIII International Scientific Conference, 1–3 June 2016, Tomsk, Russia; [proceedings]; IOP Conference Series: Materials Science and Engineering (2016, 2016)
Title screen